Eutrichosomellini (Hymenoptera: Chalcidoidea: Aphelinidae) from India, with description of two new genera - Hayat, Mohammad (Zootaxa, 2014)
Two new genera and four new species of the aphelinid tribe Eutrichosomellini (Chalcidoidea: Aphelinidae: Aphelininae) are described from India. These are Umairia Hayat gen. nov., Zubairia Hayat gen. nov., U. laiba Hayat sp. nov., U. zeera Hayat sp. nov., Z. mirifica Hayat sp. nov., and Eutrichosomella veenakumariae Hayat sp. nov. Two of the species, U. laiba and E. veenakumariae, are reared respectively from the eggs of Papilio polytes L. (Lepidoptera) and cockroach oothecae (Blattodea). Keys to the genera of the tribe Eutrichosomellini, and to the Indian species of Eutrichosomella Girault are given.